Amalgamation and characterization of graphene-calcium titanate composite for electrochemical studies. (2021) - Ramkumar, R.; Jagan, G.; Nivedha, A.K.; Krishna Priya, S.; Selvi, A.
Abstract: Graphene is a proficient anode material for super capacitors. A few reasons can be credited to the current enthusiasm for graphene as a special morphology carbon material with potential for electrochemical vitality stockpiling applications. Graphene has predominant electrical conductivity than graphite and different allotropes of carbon due to its high surface region and substance resilience. In this work, Graphene Oxide was blended by adjusted Hummer's strategy and it was decreased to graphene utilizing hydrazine hydrate. Graphene-Calcium titanate composites were set up by arrangement blending technique. Moreover, its morphology and properties were portrayed by X-beam diffraction (XRD), filtering electron magnifying instrument (SEM), Fourier change infrared spectroscopy (FT-IR), and electro-synthetic estimations. The as-arranged nano composites were tried for its super capacitance property by cyclic voltammetric (CV) explore in 2 M KOH electrolyte. CV was performed at an expected scope of 0.6 to – 0.6 V at 100 mV/s examine rate, and results show a great capacitive conduct of the nano composites.